Trends and Challenges in Maritime Energy Management (Cham : Springer International Publishing, 2018)
This book provides an overview of contemporary trends and challenges in maritime energy management (MEM). Coordinated action is necessary to achieve a low carbon and energy-efficient maritime future, and MEM is the prevailing framework aimed at reducing greenhouse gas emissions resulting from maritime industry activities. The book familiarizes readers with the status quo in the field, and paves the way for finding solutions to perceived challenges. The 34 contributions cover six important aspects: regulatory framework; energy-efficient ship design; energy efficient ship and port operation; economic and social dimensions; alternative fuels and wind-assisted ship propulsion; and marine renewable energy. This pioneering work is intended for researchers and academics as well as practitioners and policymakers involved in this important field. .
Part I Regulations: Challenges and Opportunities -- Part II Energy Efficient Ship Design -- Part III Energy Efficient Ship and Port Operation -- Part IV Economics and Social Dimensions of Maritime Energy Management -- Part V Alternative Fuels and Wind-Assisted Ship Propulsion -- Part VI Marine Renewable Energy.
Law and Criminology
text file PDF
Keywords: International environmental law; Energy policy; Energy and state; Transportation; Energy systems; Climate change